The calpain inhibitor A-705253 attenuates alcohol-seeking and relapse with low side-effect profile - Vengeliene, Valentina; Sommer, Wolfgang H.; Spanagel, Rainer (Neuropsychopharmacology, 2016)
Preclinical studies revealed contribution of N-methyl-D-aspartate receptors (NMDARs) to a variety of neuropsychiatric diseases including alcoholism, but development of NMDAR antagonists for therapeutic use has been a challenge, in part due to severe side effects. One of the key intracellular events resulting from stimulation of NMDAR is activation of calpains-calcium-dependent cysteine proteases. Here we studied whether inhibition of calpains would produce therapeutic-like effects of NMDAR antagonists but without their NMDAR-mediated side-effect profile. The calpain inhibitor A-705253 (3-10 mg/kg) was tested in a model of cue-induced reinstatement of alcohol-seeking behavior in post-dependent Wistar rats and in an alcohol deprivation effect (ADE) model in long-term alcohol drinking Wistar rats, two behavioral models for alcohol-seeking and relapse, respectively. We also tested the effect of A-705253 on the saccharine deprivation effect (SDE) as a selectivity measure. Acute treatment with A-705253 dose-dependently reduced cue-induced reinstatement of alcohol-seeking behavior. Repeated administration of A-705253 caused significant reductions of relapse-like excessive alcohol intake during the post-abstinence drinking days, an effect that persisted during two more successive drug-free drinking weeks, which was selective for the ADE as the SDE was unaffected. However, A-705253 did not produce psychostimulant, cognition impairing (delayed-matching-to-position), or psychotomimetic effects (specifically, phencyclidine discriminative stimulus effects). Taken together, these results demonstrate the involvement of calpains in alcohol-seeking and relapse and present a rationale for a novel pharmacological intervention that may reduce craving and relapse with minimal side effects in alcohol-dependent patients.
Gesehen am 27.03.2019
Published online 16 September 2015